Neuroeconomic Foundations of Trust and Social Preferences: Initial Evidence - Fehr, Ernst; Fischbacher, Urs; Kosfeld, Michael (American Economic Review, 2005)
Neuroeconomic Foundations of Trust and Social Preferences: Initial Evidence by Ernst Fehr, Urs Fischbacher and Michael Kosfeld. Published in volume 95, issue 2, pages 346-351 of American Economic Review, May 2005